The Use of Zebrafish Xenotransplant Assays to Analyze the Role of lncRNAs in Breast Cancer - Zampedri, Cecilia; Martínez-Flores, Williams Arony; Melendez-Zajgla, Jorge (Frontiers in Oncology, 2021)
Breast cancer represents a great challenge since it is the first cause of death by cancer in women worldwide. lncRNAs are a newly described class of non-coding RNAs that participate in cancer progression. Their use as cancer markers and possible therapeutic targets has recently gained strength. Animal xenotransplants allows for in vivo monitoring of disease development, molecular elucidation of pathogenesis and the design of new therapeutic strategies. Nevertheless, the cost and complexities of mice husbandry makes medium to high throughput assays difficult. Zebrafishes (Danio rerio) represent a novel model for these assays, given the ease with which xenotransplantation trials can be performed and the economic and experimental advantages it offers. In this review we propose the use of xenotransplants in zebrafish to study the role of breast cancer lncRNAs using low to medium high throughput assays.